CALLOUS UNEMOTIONAL TRAITS DAN PENGGUNAAN MEDIA SOSIAL TERHADAP TINDAKAN CYBERBULLYING - Kerap, Fransisca; Langelo, Wahyuny; Oroh, Cindi T. M. (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2026)
Introduction: Cyberbullying refers to harassment perpetrated through social media platforms, which can elicit a wide range of detrimental psychological, physical, and psychosocial consequences. The personality aspect of callous-unemotional (CU) traits has been identified as a potential contributing factor to Cyberbullying behavior. Objective: This study aims to examine the relationship between callous-unemotional traits, social media use, and Cyberbullying behavior among vocational high school students. Methods: This study employed a quantitative research design with a cross-sectional correlational approach. The research was conducted at SMK Negeri 6 Manado, targeting the entire student body as the study population. A sample of 283 respondents was selected utilizing a non-probability, purposive sampling technique. Data analysis was performed using the Chi-Square statistical test with a significance level of α = 0.05. Results: The analysis of the relationship between callous-unemotional traits and Cyberbullying yielded a p-value = 1.00. Conversely, the analysis concerning social media use and Cyberbullying demonstrated a significant association with a p-value = 0.008. Conclusion: There is no significant relationship between callous-unemotional traits and Cyberbullying behavior. However, a significant relationship exists between social media use and Cyberbullying behavior among students at SMK Negeri 6 Manado.